Effect of gellan, xanthan or locust bean gum and/or emulsified maize oil on proteins edible films properties - Rodríguez-Huezo, Erick C. Téllez-Rangel, Eva; Totosaus, Alfonso (Emirates Journal of Food and Agriculture, 2018)
Composite edible films properties depend on the functionality of the different components employed, like protein and/or polysaccharides, and/or lipids, in order to enhance mechanical properties. Collagen and egg white albumin edible films were elaborated with three different gums (locust bean gum, gellan gum or xanthan gum), with or without emulsified oil. Egg white albumin edible films were more opaque, less permeable and less soluble than collagen samples. Collagen edible films were tougher and ductile/extensible than egg white albumin samples. Emulsified oil increased opacity and decrease water vapor permeability. Although inherent differences related to protein type on water vapor permeability and mechanical properties, gellan and xanthan gums improved mechanical properties resulting in more resistant samples. Water vapor permeability was higher in samples with no-charged polysaccharide, locust bean gum, where other kind of interactions different to electrostatic ones occurred. Changes due to the presence of a lipid phase increased all tensile parameters of emulsified films based are due to strong interaction between the biopolymers and the lipid particles as a cross-linking effect.